Does the weight of basketball shoes affect speed and jumping performance? - B. Köse (Physical Education of Students, 2018)
Purpose: The objective of this study was to analyze the effect of different weights of basketball shoes on speed and jumping performance in male basketball players. Methods: 20 male basketball players in two groups, as eyes open (n:10) and eyes closed (n:10) participated in the study. The two groups performed vertical jump (VJ) and 10m sprint tests with three different weights of shoes (light, 352g; medium, 510g; heavy, 637g). The data were analyzed with Friedman repeated measurements variance analysis. Results: In Vertical Jump test, jumping performance of the eyes open group (EOG) with light shoes was found to be statistically higher as 1.8% and 2.1%, respectively when compared with medium and heavy shoes (p< 0.001). In eyes closed group (ECG), no statistically significant difference was found between any of the 3 shoe weights in vertical jump performance (p>0.005). In 10 meter (m) sprint test, 10 m sprint time of the eyes open group was found to be statistically better as 0.5% and 1.6%, respectively when compared with medium and heavy shoe performance (p<0.001). Medium weight shoe was found to be 1.2% statistically better than heavy shoes (p<0.001). In eyes closed group, light shoes affected 10m sprint performance statistically better with 1% when compared with heavy shoes (p<0.001). Conclusions: Wearing light shoes in basketball has 2.1% and 1.6% positive effect on jumping and sprint performance, respectively. It can increase basketball players’ performance. Choosing light shoes will help provide both psychological and physical advantages.